(untitled) (Historia, 2023)
This article examines colonial rhetoric, white traders, and African elite viewpoints on cooperative societies and African entrepreneurship during the Native Trade and Production Commission of Inquiry of 1944, known as the Godlonton Commission. It argues that some officials of the Native Affairs Department advocated African cooperative societies as a means of marketing African crops while others were sceptical of the entrepreneurial ability of Africans. It further argues that white traders, represented by powerful business associations, appropriated the derogatory colonial rhetoric on African entrepreneurship to defend their interests in the African reserves. The testimonies of African elites who gave evidence to the Godlonton Commission were mixed. While some supported the idea of African cooperatives, others rejected it preferring that the state support African traders against white traders in the African reserves. Cumulatively, the sentiments aired at the Godlonton Commission contributed to the colonial disinterest in cooperative societies and African entrepreneurship during the post-Second World War period. The article contributes to our historical understanding of African entrepreneurship during the 1940s, and of cooperative societies and the Godlonton Commission in general. The study uses the evidence presented to the Godlonton Commission, its final report, and other archival documents.